Heavy Metal Content in Scalp Hair of People Living in Fluorspar Mining Belt in Elgeyo Marakwet County, Kenya - Olero, J. N. Kemboi; Simiyu, G. M.; Kipkorir, E. C.; Wakhisi, J. (Africa Environmental Review Journal, 2018)
Human hair is a stable matrix that presents many advantages as a bioindicator of exposure to contaminants. Levels of Arsenic, Cadmium, Chromium and Lead in scalp hair of people in Upper, Middle and Lower Kimwarer zones in Fluorspar mining belt were determined using the Atomic Absorption Spectrophotometer (AAS) for Cadmium, Chromium and Lead but for Arsenic, Vapour Generating Atomic, Absorption Spectrophotometer was used. The levels of the heavy metals were discussed basing on their concentrations in food crops and water consumed by the inhabitants within the mining belt. Results showed the highest level of the metals was Pb, with an average concentration of 2.83±0.50mg/kg, followed by Cr (2.81±0.62 mg/kg), As (2.73±0.50 mg/kg), and Cd (1.53±0.28 mg/kg), following a decreasing order of Pb > Cr > As > Cd. Arsenic and Lead concentration in Upper and Lower Kimwarer and in Middle and Lower Kimwarer results showed a significant difference in (p<0.05, α=0.05). Cadmium and Chromium levels in all the sites had no significant difference p=0.133 and p=0.290 respectively. There was, however a significant correlation (p<0.01) between Pb concentration in milk and the Pb levels in scalp hair. This study provides information on levels of heavy metals in hair which implies their exposure occurred through ingestion of contaminated maize, beans, millet, water and milk in the study area. Given heavy metal levels in the scalp hair the people living within the mining belt could be at risk of adverse health risks from heavy metal exposure. Therefore, the results of this study can be used to analyze the internal heavy metal burden in the resident population of Kimwarer sub-catchment and can also serve as reference for further studies.